Elaine Ye: capstone - Ye, Elaine, artist (Colorado State University. Libraries, 2025)
The artist's statement: As a Chinese American artist, I experiment with animation, 3D modeling, coding, 3D printing, painting, drawing, and collage art. My artwork is about my identity and my experiences as both a Chinese person and an American. Sometimes there are some frustrating aspects of growing up in two worlds. Imagine trying to fit into both the world of Chinese traditions at home and the world of American pop culture outside. It's like being two people in one body, but you have to accept who you are no matter where you are. I often make art that mixes traditional Chinese elements, like dragons and food, with things that feel super American, like cartoons and video games. It's my way of poking fun at the stereotypes people have about Asians. Sometimes, I use bright colors and silly shapes to turn these stereotypes into something that makes you laugh and think of who I am. Such as my artwork, the Translucent Dragon Cloud Islands or "June in Japan". Which mixes traditional Chinese painting ink styles into animation or 3D modeling. Being a Chinese American means balancing expectations. Sometimes people think I should be this quiet, hardworking kid who loves to study, while I just want to be myself. My art is my way of saying, "Hey, I'm not just one thing. I'm a mix, and that's cool!" It's like creating a new world where it is being celebrated, not just tolerated. I am a dramatic, childish, weird, nerdy otaku who loves anime, Disney, musicals, and video games. Someone who loves both the old traditional artwork making and the new technological-electrical form of artwork, mixing both together.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art